ENHANCEMENT WOOD CARVING IN PRODUCING PREMIUM PRODUCT - Muhammad Reduan Isahak; Raja Nafida Raja Shahminan; Fadhlina Ahmad@Taufik (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Engraving is a process of sculpting, carving and scratching a pattern. In ancient times the art of wood carving became a symbol of status of noble and courtiers. According to Halim Nasir (1986) the courtiers and sultans became patrons to revive the glory of wood carving. This shows that wood carving is high dignity. The Malays emphasizes every work of art and is designed by the soul attempts to communicate with the public in feel, thinking and interpretations, (Nazzri, 2016). However, the price of traditional wood carving product is too high and difficult to educate the public to love wood carving products. The discrepancy between the two modern and traditional industries makes the development of sculpture difficult to compete with modern products. Besides that, wood carving is also used at will in its placement in the design. This study will lead to several main objectives among which is to know the issues faced by these two industries and know the correct placement of carving in the design so as not to violate its philosophy and ethics. Methodology of the study is using interview data and ethnography with master craft. This research and development will involve ten members of timber manufacturing company around Malaysia which is from modern and traditional timber product companies. This research was conducted for 5 days from 14th -18th October 2020 in Temerloh, Pahang. Through this research found three mains issue they facing in order to preserve the wood carving and culture in product and design. The traditional wood carving can be applied on furniture or equipment and preserve the philosophy trough educate the modern practitioner and involvement of ‘pandai kayu’. The application of heritage in the first phase is very important so that it reaches the community indirectly and is not considered outdated.